Exploring the depths of the rainforest: a metaphor for teaching critical reflection. Issue 2 (4th March 2019) - Reimer, Elizabeth Claire; Whitaker, Louise
ABSTRACT: Many social welfare and social work students struggle to demonstrate competence in the complex process of critical reflection through to the stage of transformed thinking and action. Examples of how students learn critical reflection as an interpretive experience are scarce. This paper presents, as a case study, the process one of the authors experienced while critically reflecting on teaching critical reflection. The paper explores how this approach unlocked disturbing insights into how personally held values, views and knowledge influenced her performance relating to teaching critical reflection. Experiencing what she asks of her students raised questions regarding the duty of care that social welfare and social work educators have to ensure their students engage in critical, and transformative, self-discovery in safe and supportive ways. We propose that in the early stages of social welfare and social work degrees, rather than assessing students' critical reflection of an event, educators examine students' capacity to learn critical reflection in a different way. Drawing on critical hermeneutics, and a theory of visual thinking, the paper outlines the cognitive map of a process of critical reflection on teaching critical reflection. We present this as a metaphor of walking through a rainforest.